Bilingualism (Journal of Parents and Teachers, 2025)
The article discusses bilingualism in Spain and the differing opinions surrounding it. Additionally, Spain is a country made up of many autonomous communities, some of which have their own dialects. This leads to the creation of bilingual programs where cultural factors are developed.
Keywords: bilinguali; Spain; dialects; culture